Prediksi Data Kesetimbangan Cair-cair Pada Sistem Terner Air + Asam Laktat + Pelarut Menggunakan Model UNIFAC-DMD - Sugiarto, Kurniawan Wahyu; Honora, Faradiba; Altway, Saidah; Zuchrillah, Daril Ridho (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Industrial lactic acid can be produced via chemical synthesis and fermentative production. However, due to the environmental issue and consumer preference, fermentative production of lactic acid is preferable. Lactic acid is used in many industries, including food processing, pharmaceutical, chemical and cosmetic industries. Various methods have been developed for separating lactic acid from its aqueous solution, and liquid-liquid extraction is considered as the most promising and efficient method. Liquid-liquid equilibrium data provide the basis for a rational design and optimal extraction operation. The objective of this study is to predict the liquid-liquid equilibria in the ternary systems of water+ lactic acid + solvent (MIBK, 2-pentanol, 1-hexanol) at temperatures of 303.15 K and 313.15 K and atmospheric pressure (101.3 kPa) using the UNIFAC-Dortmund (DMD) model. The distribution coefficients and separation factors were determined to evaluate the extraction performance of lactic acid. The extraction performance was in the order of MIBK > 1-hexanol > 2-pentanol. The prediction of lactic acid + water + MIBK system at 303,15 K was also compared with the experimental data with the RMSD 2,5 %. This result represented that UNIFAC-DMD was a reliable model for the prediction of liquid-liquid equilibria of system involving lactic acid.